Gradient structure magnesium-aluminum-zirconium composite refractory and preparation method thereof
Patent Information
- Application Number
- CN202411683773.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-11-22
AI Technical Summary
然而,如何将抗侵蚀性能好的MgO-Al2O3-ZrO2材料和抗热震性能好的Al2Zr3C4-MgAlON-MgAl2O4材料集成一体,制备高性能的功能梯度材料,还未见报道
[0026]本发明创新地利用高温下铝锆合金对氧分压地敏感特性,设计原位合成、梯次反应路径,制备一种新型的梯度结构镁铝锆复合耐火材料,其外层为致密的MgAl2O4-Al2O3-ZrO2复合材料,可有效提高材料的抗侵蚀性能;其内部为多孔的Al2Zr3C4-MgAlON增强MgAl2O4复合材料,可有效提高材料的抗热震性能。该具有“高抗侵蚀工作层—抗热震内部区”功能梯度特征的新型耐火材料在有色金属冶炼炉、RH精炼炉中具有广泛的应用前景。
Smart Images

Figure CN119569437B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refractory materials technology, specifically relating to a gradient structure magnesium aluminum zirconium composite refractory material and its preparation method. Background Technology
[0002] Refractory materials are crucial foundational and supporting materials in high-temperature industries. During high-temperature service, refractory materials endure severe thermal shock, chemical erosion by complex media, and mechanical wear, requiring a balance of excellent thermal shock resistance, erosion resistance, and high mechanical strength. However, the key service properties of refractory materials are often interdependent. For example, excellent erosion resistance requires a dense structure, but this sacrifices thermal shock resistance; conversely, excellent thermal shock resistance requires a certain amount of porosity to alleviate thermal stress, but this reduces the material's strength and may exacerbate the penetration and erosion of the medium into the material's interior. Designing composite material compositions and gradient structures based on the different service microenvironments of refractory products, such as the cold and hot surfaces, to achieve zonal enhancement of key service properties is an important direction for developing high-performance, long-life, and functionalized advanced refractory materials. Taking refractory products such as ladle slides for continuous casting and RH refining furnace linings as examples, their hot surfaces directly bear the scouring and erosion of high-temperature molten steel, requiring excellent resistance to scouring and erosion; while the extreme temperature difference between the cold and hot surfaces and the uneven stress distribution make the internal thermal shock resistance of the product particularly important. Developing novel refractory materials with functional gradient characteristics of "high erosion-resistant working layer - thermal shock-resistant internal zone" through composite material composition and structural gradient design has become a current research hotspot.
[0003] Magnesium aluminum spinel possesses excellent high-temperature performance and is an important oxide refractory material, but its erosion resistance is poor. Studies have shown that introducing ZrO2 into magnesium aluminum spinel materials can significantly improve the mechanical properties and erosion resistance of MgAl2O4. This is because ZrO2 can react with CaO, the main chemical component in slag, to form the high-melting-point phase CaZrO3, creating a dense layer that prevents further slag penetration. Chinese Patent (Application No.: CN202311775105.X) "A MgO-Al2O3-ZrO2 Refractory Brick and its Preparation Method" discloses a novel MgO-Al2O3-ZrO2 refractory brick for non-ferrous metal smelting furnaces, characterized by highly dispersed ZrO2 and MgAl2O4. This brick exhibits excellent erosion resistance and high-temperature mechanical properties, making it suitable for refractory products used in non-ferrous metal smelting and iron and steel smelting, and can significantly extend the service life of non-ferrous metal smelting furnaces and RH refining furnaces. However, since this system is a pure oxide system with low thermal conductivity, its thermal shock resistance still has considerable room for improvement. Especially for large-sized refractory products used in furnace linings such as RH refining furnaces and non-ferrous metal smelting furnaces, the internal temperature gradient is large, leading to stress concentration and making cracks easily formed. Therefore, the internal thermal shock resistance of the product is a key factor determining its service life.
[0004] In terms of material composition, non-oxide Al2Zr3C4 and MgAlON exhibit high thermal conductivity and low coefficients of thermal expansion, resulting in excellent thermal shock resistance. Structurally, their porous structure effectively alleviates stress concentration. Therefore, in-situ synthesis of Al2Zr3C4 and MgAlON reinforcing phases within an oxide matrix, forming a robust ceramic bond, can significantly improve both the high-temperature mechanical properties and thermal shock resistance of the material. However, the integration of erosion-resistant MgO-Al2O3-ZrO2 materials with thermally shock-resistant Al2Zr3C4-MgAlON-MgAl2O4 materials to prepare high-performance functionally graded materials remains unreported. Summary of the Invention
[0005] To overcome the bottleneck of existing technologies where it is difficult to simultaneously achieve both corrosion resistance and thermal shock resistance, this invention proposes utilizing the sensitivity of aluminum-zirconium alloys to oxygen partial pressure at high temperatures. An in-situ synthesis and step-by-step reaction pathway ("passive oxidation" → "active oxidation" → "direct nitriding / carburization") is designed to prepare a novel gradient-structured magnesium-aluminum-zirconium composite refractory material. Its outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material, which effectively improves the material's corrosion resistance; its interior is a porous Al2Zr3C4-MgAlON-reinforced MgAl2O4 composite material, which effectively improves the material's thermal shock resistance. This novel refractory material, with its functional gradient characteristics of a "highly corrosion-resistant working layer—thermal shock-resistant internal zone," has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0007] A gradient-structured magnesium-aluminum-zirconium composite refractory material is characterized in that its outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material with a thickness of 0.1-5 mm and a porosity of ≤5%, and its interior is a MgAl2O4-MgAlON-Al2Zr3C4-AlZr composite material with a porosity of 10%-20%.
[0008] Furthermore, the gradient structure of the magnesium-aluminum-zirconium composite refractory material comprises the following raw material composition by mass percentage: 70%–95% magnesium-aluminum spinel, 5%–30% zirconium-aluminum alloy, plus 2%–5% phenolic resin binder.
[0009] Furthermore, the magnesium aluminum spinel raw material comprises aggregates with particle sizes of 3-1 mm and <1 mm and fine powders with particle sizes of ≤0.08 mm, wherein the mass percentage of the magnesium aluminum spinel aggregates with particle sizes of 3-1 mm and <1 mm is 65%-90%, and the mass percentage of the magnesium aluminum spinel fine powder is 5-30%; the zirconium aluminum alloy raw material is fine powder with a particle size of ≤0.1 mm.
[0010] Preferably, the main chemical components of the zirconium-aluminum alloy raw material are Ti and Al elements, with Zr content ranging from 10% to 50% and Al content ranging from 50% to 90% by mass percentage.
[0011] The preparation method of the gradient structure magnesium-aluminum-zirconium composite refractory material includes the following steps:
[0012] (1) Weigh the magnesium aluminum spinel, zircon aluminum alloy and binder according to the proportion, stir them evenly and make mud;
[0013] (2) Place the clay material from step (1) into a press and press it into shape to obtain a green body;
[0014] (3) Place the green body from step (2) in a tunnel kiln and dry it at 150℃~200℃ for 12~24 hours to reduce the residual moisture to less than 1.5%;
[0015] (4) Place the dried brick blanks in a tunnel kiln and fire them at 1350℃~1750℃ in air atmosphere for 3~8 hours.
[0016] The principle of this invention: During the high-temperature firing process, the oxygen partial pressure on the outer layer of the brick blank is relatively high, and the aluminum-zirconium alloy in the composite material preferentially undergoes a passive oxidation reaction, as shown in formula (1), generating Al2O3 and ZrO2 in situ. On the one hand, this reaction is accompanied by volume expansion, and the reaction products Al2O3 and ZrO2 fill the pores, promoting densification; on the other hand, the newly formed Al2O3 and ZrO2 have strong reactivity, and further dissolve into magnesium aluminum spinel at high temperature, as shown in formula (2), generating the MAZ ternary metastable phase, which decomposes during cooling to produce MgAl2O4-Al2O3-ZrO2 eutectic, thereby achieving a highly uniform and finely dispersed ZrO2 phase and fully utilizing the erosion resistance of the ZrO2 phase.
[0017] AlZr + O2 → Al2O3 + ZrO2 (1)
[0018] MgAl₂O₄ + Al₂O₃ + ZrO₂ → Mg 5+x Al 2.4-x Zr 1.7+0.25x O 12 (2)
[0019] The passive oxidation of the aluminum-zirconium alloy in the outer layer of the product consumes a large amount of O2 in the atmosphere, and the oxygen partial pressure inside the product gradually decreases. Under high temperature and low oxygen partial pressure conditions, the aluminum-zirconium alloy inside the product begins to undergo an active oxidation reaction, as shown in equation (3), generating Al. x O y The gas phase further diffuses to the surface of the product, where it oxidizes and deposits on the surface layer with high oxygen partial pressure, further promoting the densification of the product surface.
[0020] Al [AlZr] + O2 → Al x O y (g) (3)
[0021] As the passive oxidation and active oxidation reactions of the aluminum-zirconium alloy in the outer layer of the product proceed, the oxygen partial pressure inside the product gradually decreases to an extremely low value. The aluminum-zirconium alloy reacts directly with N2 and residual carbon of phenolic resin, as shown in formula (4), to generate AlN and Al2Zr3C4 in situ. AlN further reacts with MgAl2O4 spinel, as shown in formula (5), to generate the MgAlON reinforcing phase.
[0022] AlZr + N2 + C → AlN + Al2Zr3C4 (4)
[0023] AlN + MgAl2O4 → MgAlON (5)
[0024] By utilizing the stepwise changes in the reaction mechanism of aluminum-zirconium alloy from the outside to the inside of the product—passive oxidation → active oxidation → direct nitriding / carburization—a magnesium-aluminum-zirconium composite refractory material with a gradient structure of "dense MgAl2O4-Al2O3-ZrO2 anti-erosion layer" — "high-strength MgAlON and Al2Zr3C4 co-reinforced MgAl2O4 composite thermal shock resistant zone"—a magnesium-aluminum-zirconium composite refractory material was prepared. Figure 2 As shown. (Attachments cannot appear in the instruction manual; they can only be included in the accompanying drawings of the instruction manual.)
[0025] The present invention also provides a gradient structure magnesium aluminum zirconium composite refractory material, which is obtained by the preparation method of the present invention and has excellent high temperature strength, thermal shock resistance and erosion resistance.
[0026] This invention innovatively utilizes the sensitivity of aluminum-zirconium alloys to oxygen partial pressure at high temperatures, designing an in-situ synthesis and step-by-step reaction pathway to prepare a novel gradient-structured magnesium-aluminum-zirconium composite refractory material. Its outer layer is a dense MgAl₂O₄-Al₂O₃-ZrO₂ composite material, effectively improving the material's corrosion resistance; its interior is a porous Al₂Zr₃C₄-MgAlON-reinforced MgAl₂O₄ composite material, effectively improving the material's thermal shock resistance. This novel refractory material, possessing a functional gradient characteristic of "high corrosion-resistant working layer—thermal shock-resistant internal zone," has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.
[0027] Beneficial Effects: Addressing the challenge of simultaneously achieving both corrosion resistance and thermal shock resistance in existing technologies, this invention utilizes the sensitivity of aluminum-zirconium alloys to oxygen partial pressure at high temperatures. By designing an in-situ synthesis and step-reaction pathway, a novel gradient-structured magnesium-aluminum-zirconium composite refractory material with a "dense corrosion-resistant layer - non-oxide-reinforced thermal shock-resistant zone" is prepared. Details are as follows:
[0028] (1) The outer layer of this gradient-structured magnesium-aluminum-zirconium composite material is a dense MgAl2O4-Al2O3-ZrO2 composite material with a porosity of ≤5%, which can effectively improve the material's corrosion resistance. The inner layer is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material with a porosity of 10% to 20%, which can effectively improve the material's thermal shock resistance. This novel refractory material with the functional gradient characteristics of "high corrosion-resistant working layer - thermal shock-resistant inner zone" achieves a synergistic improvement in corrosion resistance and thermal shock resistance, and has broad application prospects in non-ferrous metal smelting furnaces and RH refining furnaces.
[0029] (2) The outer layer of the product is a dense MgAl2O4-Al2O3-ZrO2 composite material, in which the ZrO2 phase is highly uniformly and finely dispersed. On the one hand, the highly finely dispersed active ZrO2 can quickly capture the main component of the molten slag, CaO, improving the reaction efficiency between the two and thus improving the erosion resistance; on the other hand, the dense structure can greatly reduce the penetration of molten slag into the interior of the product, thereby improving the erosion resistance. At the same time, the thickness of this dense layer is about 0.1 to 5 mm, which serves as a working layer to resist erosion without affecting the thermal shock resistance of the product.
[0030] (3) The interior of the product is a porous Al2Zr3C4-MgAlON reinforced MgAl2O4 composite material. The Al2Zr3C4 and MgAlON reinforced phases synthesized in situ have excellent thermal conductivity and low thermal expansion coefficient, which can greatly alleviate the stress concentration caused by temperature gradient and improve the thermal shock resistance of the material.
[0031] (4) The preparation method of the present invention is simple, has high production efficiency, is suitable for industrial production, and has a high qualification rate. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 This is a flowchart of the preparation method of the present invention;
[0034] Figure 2 This is a schematic diagram of the structure of the material of the present invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be described in detail below with reference to specific embodiments. It should be understood that the embodiments described in this specification are merely illustrative and not intended to limit the scope of the invention.
[0036] Example 1
[0037] 65 wt.% magnesium-aluminum spinel aggregate, 5 wt.% magnesium-aluminum spinel fine powder, and 30 wt.% aluminum-zirconium alloy fine powder were mixed, and 3 wt.% phenolic resin binder was added to the above mixture. The mixture was kneaded evenly, pressed into shape to obtain a MgAl2O4-AlZr composite material green body, and dried at 150℃ for 24 hours. The dried green body was heated to 1350℃ at a heating rate of 10℃ / min and held for 8 hours to obtain a gradient-structured magnesium-aluminum-zirconium composite refractory material.
[0038] The obtained gradient-structured magnesium-aluminum-zirconium composite refractory material was tested and found to have a dense layer thickness of approximately 2 mm. The main phase composition of the dense layer is MgAl2O4, Al2O3, and ZrO2, with a porosity of 4.0%. The main phase composition of the interior is MgAl2O4, MgAlON, and Al2Zr3C4, with a porosity of 15.2%. The product has a room temperature compressive strength of 216 MPa and a thermal shock resistance (water cooling at 1100℃) of ≥25 cycles.
[0039] Example 2
[0040] 75 wt.% magnesium-aluminum spinel aggregate, 5 wt.% magnesium-aluminum spinel fine powder, and 20 wt.% aluminum-zirconium alloy fine powder were mixed, and 3.5 wt.% phenolic resin binder was added to the above mixture. The mixture was kneaded evenly, pressed into shape to obtain a MgAl2O4-AlZr composite material green body, and dried at 200℃ for 12 hours. The dried green body was heated to 1550℃ at a heating rate of 10℃ / min and held for 5 hours to obtain a gradient-structured magnesium-aluminum-zirconium composite refractory material.
[0041] The obtained gradient-structured magnesium-aluminum-zirconium composite refractory material was tested and found to have a dense layer thickness of approximately 3 mm. The main phase composition of the dense layer is MgAl2O4, Al2O3, and ZrO2, with a porosity of 3.2%. The main phase composition of the interior is MgAl2O4, MgAlON, and Al2Zr3C4, with a porosity of 14.3%. The product has a room temperature compressive strength of 234 MPa and a thermal shock resistance (water cooling at 1100℃) of ≥25 cycles.
[0042] Example 3
[0043] 90 wt.% magnesium-aluminum spinel aggregate, 5 wt.% magnesium-aluminum spinel fine powder, and 5 wt.% aluminum-zirconium alloy fine powder were mixed, and 3 wt.% phenolic resin binder was added to the above mixture. The mixture was kneaded evenly, pressed into shape to obtain a MgAl2O4-AlZr composite material green body, and dried at 180℃ for 15 hours. The dried green body was heated to 1750℃ at a heating rate of 10℃ / min and held for 3 hours to obtain a gradient-structured magnesium-aluminum-zirconium composite refractory material.
[0044] The obtained gradient-structured magnesium-aluminum-zirconium composite refractory material was tested and found to have a dense layer thickness of approximately 2 mm. The main phase composition of the dense layer is MgAl2O4, Al2O3, and ZrO2, with a porosity of 4.7%. The main phase composition of the interior is MgAl2O4, MgAlON, and Al2Zr3C4, with a porosity of 16.7%. The product has a room temperature compressive strength of 198 MPa and a thermal shock resistance (water cooling at 1100℃) of ≥25 cycles.
[0045] Example 4
[0046] 80 wt.% magnesium-aluminum spinel aggregate, 10 wt.% magnesium-aluminum spinel fine powder, and 10 wt.% aluminum-zirconium alloy fine powder were mixed, and 3.5 wt.% phenolic resin binder was added to the above mixture. The mixture was kneaded evenly, pressed into shape to obtain a MgAl2O4-AlZr composite material green body, and dried at 180℃ for 15 hours. The dried green body was heated to 1750℃ at a heating rate of 10℃ / min and held for 3 hours to obtain a gradient-structured magnesium-aluminum-zirconium composite refractory material.
[0047] The obtained gradient-structured magnesium-aluminum-zirconium composite refractory material was tested and found to have a dense layer thickness of approximately 2 mm. The main phase composition of the dense layer is MgAl2O4, Al2O3, and ZrO2, with a porosity of 3.5%. The main phase composition of the interior is MgAl2O4, MgAlON, and Al2Zr3C4, with a porosity of 14.7%. The product has a room temperature compressive strength of 238 MPa and a thermal shock resistance (water cooling at 1100℃) of ≥25 cycles.
[0048] Example 5
[0049] 80 wt.% magnesium-aluminum spinel aggregate, 5 wt.% magnesium-aluminum spinel fine powder, and 15 wt.% aluminum-zirconium alloy fine powder were mixed, and 4 wt.% phenolic resin binder was added to the above mixture. The mixture was kneaded evenly, pressed into shape to obtain a MgAl2O4-AlZr composite material green body, and dried at 180℃ for 15 hours. The dried green body was heated to 1750℃ at a heating rate of 10℃ / min and held for 3 hours to obtain a gradient-structured magnesium-aluminum-zirconium composite refractory material.
[0050] The obtained gradient-structured magnesium-aluminum-zirconium composite refractory material was tested and found to have a dense layer thickness of approximately 2 mm. The main phase composition of the dense layer is MgAl2O4, Al2O3, and ZrO2, with a porosity of 4.1%. The main phase composition of the interior is MgAl2O4, MgAlON, and Al2Zr3C4, with a porosity of 14.8%. The product has a room temperature compressive strength of 212 MPa and a thermal shock resistance (water cooling at 1100℃) of ≥25 cycles.
[0051] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this invention, and these modifications or substitutions should all be covered within the scope of protection of this invention. Therefore, the scope of protection of this invention should be determined by the scope defined in the claims.
Claims
1. A gradient-structured magnesium-aluminum-zirconium composite refractory material, characterized in that, Its outer layer is a dense MgAl2O4-Al2O3-ZrO2 composite material with a thickness of 0.1-5 mm and a porosity of ≤5%, while its interior is a MgAl2O4-MgAlON-Al2Zr3C4-AlZr composite material with a porosity of 10%-20%.
2. The gradient-structured magnesium-aluminum-zirconium composite refractory material according to claim 1, characterized in that, It comprises the following raw materials in the following weight percentages: 70%–95% magnesium aluminum spinel, 5%–30% zirconium aluminum alloy, plus 2%–5% phenolic resin binder.
3. The gradient-structured magnesium-aluminum-zirconium composite refractory material according to claim 2, characterized in that, The magnesium aluminum spinel raw material includes aggregates with particle sizes of 3-1 mm and <1 mm and fine powders with particle sizes of ≤0.08 mm, wherein the mass percentage of magnesium aluminum spinel aggregates with particle sizes of 3-1 mm and <1 mm is 65%-90%, and the mass percentage of magnesium aluminum spinel fine powder is 5-30%; the zirconium aluminum alloy raw material is fine powder with a particle size of ≤0.1 mm.
4. The gradient-structured magnesium-aluminum-zirconium composite refractory material according to claim 2 or 3, characterized in that, The main chemical components of the zirconium-aluminum alloy raw material are Ti and Al elements. By mass percentage, the Zr element content is 10% to 50%, and the Al element content is 50% to 90%.
5. The method for preparing the gradient-structured magnesium-aluminum-zirconium composite refractory material according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Weigh the magnesium aluminum spinel, zircon aluminum alloy and binder according to the proportion, stir them evenly and make mud; (2) Place the clay material from step (1) into a press and press it into shape to obtain a green body; (3) Place the green body from step (2) in a tunnel kiln and dry it at 150℃~200℃ for 12~24 hours to reduce the residual moisture to less than 1.5%; (4) Place the dried brick blanks in a tunnel kiln and fire them at 1350℃~1750℃ in air atmosphere for 3~8 hours.
Citation Information
Patent Citations
MgO-Al2O3-ZrO2 refractory brick and preparation method thereof
CN117865697A
Magnesium-aluminum-zirconium composite spinel refractory material
CN102093063A
Resin-bonded aluminum-magnesium refractory material
CN102775171A